2019
DOI: 10.1002/dvdy.98
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Lin28a delays Xenopus metamorphosis and down‐regulates albumin independently of its translational regulation domain

Abstract: Background Lin28 regulates stem cell biology and developmental timing. At the molecular level Lin28 inhibits the biogenesis of the micro RNA let‐7 and directly controls the transcription and translation of several genes. In Xenopus, Lin28 overexpression delays metamorphosis and affects the expression of genes of the thyroid hormone (TH) axis. The TH carrier albumin, synthesized by the liver, is down‐regulated in limbs and tail after Lin28 overexpression. The molecular mechanisms underlying the interaction betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…For example, studies have shown that humans utilize thyroid hormones T3 and T4, important endocrine modulators in amphibian metamorphosis, during the pre to postnatal transition period [173][174][175]. Additionally, studies have found that a genetic loci involved in the metamorphic timing of C. elegans and Xenopus laevis is conserved in humans for the modulation of sexual maturation [176][177][178]. Evidence of these shared mechanisms suggests a closer tie between metamorphosis and human growth and maturation than previously considered, and it may be an important route of exploration in the future.…”
Section: Transformation Toward An Adult Patterningmentioning
confidence: 99%
“…For example, studies have shown that humans utilize thyroid hormones T3 and T4, important endocrine modulators in amphibian metamorphosis, during the pre to postnatal transition period [173][174][175]. Additionally, studies have found that a genetic loci involved in the metamorphic timing of C. elegans and Xenopus laevis is conserved in humans for the modulation of sexual maturation [176][177][178]. Evidence of these shared mechanisms suggests a closer tie between metamorphosis and human growth and maturation than previously considered, and it may be an important route of exploration in the future.…”
Section: Transformation Toward An Adult Patterningmentioning
confidence: 99%